An efficient depth map acquisition technology based on generalized superpixel for integral imaging. (27th October 2021) - Gu, Yue-Jia-Nan; Piao, Yan; Deng, Li-Jin; Gao, Kai
Abstract: This paper proposes a simplified method to generate elemental images using the image pair of the scene for integral imaging stereo display. Firstly, the generalized superpixel matching algorithm is designed for integral imaging to obtain the depth map. We define the discrete boundary according to the characteristics of the low-texture region. A kind of consistency check method by calculating the inclination degree of the discrete boundary is proposed. The remaining texture regions are handled by assisted growth matching method. The precise depth map is obtained through the above two steps. Secondly, the depth map and color image are used to generate multiple elemental images according to the reverse mapping principle. Therefore the reconstruction quality depends on the accuracy of the depth map. The experiments verify that the depth map has a small error range and prominent details which can improve the accuracy of the reconstructed light field and is suitable for integral imaging.